2020
DOI: 10.1007/s42773-020-00039-1
|View full text |Cite|
|
Sign up to set email alerts
|

Biochar increases soil microbial biomass with changes in extra- and intracellular enzyme activities: a global meta-analysis

Abstract: Biochar application to soil has been proposed as a potential management strategy to enhance soil carbon (C) sequestration, reduce greenhouse gas emission, improve soil quality, and increase crop productivity. The effects of biochar on soil microbial and enzyme activities are integrally linked to the potential of biochar in achieving these benefits. We conducted a global meta-analysis to assess the effects of biochar on soil microbial biomass C and nitrogen (N) and the activities of 12 enzymes, and identify key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(132 citation statements)
references
References 75 publications
11
114
4
3
Order By: Relevance
“…The correspondence analysis also revealed that improvement in soil properties such as EC, SOC, P, K, and CEC plays a dominant role in improving the soil enzyme activity. Pokharel et al [90] also observed that different levels of biochar increased UA in the soil. In another study by Mehmood et al [91], UA in the soil after 60 and 120 days of sugarcane residues biochar (10 t ha −1 ) application increased by 7.9 and 12.7% over control.…”
Section: Effect Of Organic Amendments On Smb and Enzyme Activitymentioning
confidence: 89%
“…The correspondence analysis also revealed that improvement in soil properties such as EC, SOC, P, K, and CEC plays a dominant role in improving the soil enzyme activity. Pokharel et al [90] also observed that different levels of biochar increased UA in the soil. In another study by Mehmood et al [91], UA in the soil after 60 and 120 days of sugarcane residues biochar (10 t ha −1 ) application increased by 7.9 and 12.7% over control.…”
Section: Effect Of Organic Amendments On Smb and Enzyme Activitymentioning
confidence: 89%
“…Our results revealed that UA, DHA, and BGA enzyme activities were not affected by biochar application alone but adding compost greatly enhanced their activity. While many studies have shown enhanced enzymatic activity in response to biochar [ 74 , 75 ], these results were typically collected within 100 days of biochar application. The 6-month period between biochar application and soil enzyme analyses conducted in this experiment may have contributed to a lack of significant impact of biochar alone.…”
Section: Discussionmentioning
confidence: 99%
“…Critical to further advances is the recognition and reporting of the diversity of biochars. (Lehmaan, et al 2011, andPokharel et al 2020).…”
Section: Resultsmentioning
confidence: 98%
“…Hence, farmers often face extreme poverty in drought-prone areas. Efficient water use techniques are very important in the face of climate change, (Sohi et al 2010, Clawston et al 2014, Barrow 2012and Khanmohamadi et al 2015 discourage deforestation and preserve cropland diversity (Yu et al 2013, Muhamad et al 2018, Badawi 2019 and Pokharel et al 2020).…”
Section: Introductionmentioning
confidence: 99%